Dialogical engagement with The mythopoetics of currere : extending the work of Mary Aswell Doll across theory, literature, and autobiography - Casemore, Brian (New York, NY : Routledge, 2022)
This volume showcases a series of chapters that elaborate on Mary Aswell Doll's contributions to the field of curriculum theory through her examination of currere as a mythopoetics. By bringing Doll's Jungian, autobiographical, and literary perspectives into conversation with emergent forms of subjective inquiry--including aesthetic concepts, ecological questions, and spiritual themes--the volume foregrounds the originality and significance of Doll's book The Mythopoetics of Currere in particular, while simultaneously extending it and demonstrating its applications in various scholarly conversations. Leading scholars in the field of curriculum studies such as William F. Pinar and Molly Quinn demonstrate how they use Doll's ideas as pedagogy, as theoretical framing for their work, and as the basis of their own study and self-exploration. A response essay from Doll herself concludes the text, bringing further thought and insight to the mythopoetic dimensions of currere. This text will benefit scholars, academics, and students in the fields of curriculum studies, curriculum theory, and the foundations of education more broadly. Teachers and teacher educators interested in the conceptualization of curriculum in humanities education will also benefit from this volume.
"Routledge Focus"--PDF image of cover.
Keywords: Education -- Curricula -- Philosophy; Education -- Biographical methods; Reflective learning; Doll, Mary Aswell; EDUCATION -- Curricula; EDUCATION -- Philosophy & Social Aspects